What role for the EPAs in the Caribbean? - Gasiorek, Michael (2004)
Considers the possibilities for an EPA between the European Union and the Caribbean - given the stated objectives of the EPAs and the particularities of the Caribbean region. Discusses the Caribbean economies, focusing on those aspects that are considered central to evaluating the EPAs. Analyses the likely effects of the EPA on Caribbean trade performance and hence, indirectly, on development and poverty eradication.